Anatomia foliar comparada entre indivíduos de sol e de sombra de Saranthe eichleri Petersen (Marantaceae) em dois ambientes distintos na Mata Atlântica - Espírito Santo, Alessandra do (1998)
This work deals with the morphologic and anatomic aspects of the leaf of specimens of Saranthe eichleri Petersen (Marantaceae) growing at the different degrees of luminosity in the Forest Preserve of the Tijuca and the Rio das Pedras Ecological Reserve. Both habitats are inserted in parts of the secondary forest, pertains to the mountaineer context of the Atlantic Rain Forest, State of Rio de Janeiro and differs in the forest successional stages and pluviometric regime. The presence of the hypodermis, of the "oblique-cells" in the pulvinus and the air-lacunae that extend pratically for all levels of the leaf, are characteristics of the family. The differences in the sun and shade individuals are related to: the frequency of the stomata per mm2; the number of the hypodermis layer at junction of lamina and midrib and apex; the number of the layer as well as thickness of the chlorenchyma and hypodermis in the lamina; the presence of gelatinous fibers on the specimens shaded of Forest Preserve of the Tijuca; the number of air-lacunae in the midrib and the characteristc at the margin in the material from two habitats.